Butler Matrix 4x4 untuk Aplikasi Wideband-Radar - Nadia Media Rizka; Ilfiyantri Intyas; Samsurizal Rizal (PPM Telkom University, 2019)
In this research, a 4x4 butler matrix for wideband-radar application with frequency range in S- Band (operation frequency at 3 GHz) was designed with 4 hybrid coupler and 2 crossover coupler in it. Using electromagnetic band gap (EBG) technique to increase the bandwidth by put the perforated structures (holes) at the ground plane. The research results (modelling by software application)show the design of butler matrix with characteristics of the bandwidth more than 500 MHz. In addition, the value of bandwidth enhancement is up to 259 %.